Interference management schemes for multi‐user cooperative wireless networks. Issue 9 (14th May 2015) - Omri, Aymen; Hasna, Mazen O.
Abstract: Cooperative communication is a promising technique for future wireless networks. It can be used in improving communication reliability and enhancing spectrum efficiency by using the broadcast nature of radio communication and exploiting cooperative diversity. However, its performance gain degrades in the presence of co‐channel interference, which makes it essential to propose interference mitigation schemes. In this paper, we introduce three cooperative communication schemes with interference management for multi‐user cooperative wireless networks. The first scheme (best relay selection) is used as a performance benchmark because it completely avoids the interference problem by using the Frequency‐Division Multiple Access technique. The second scheme (best available relay selection) maximizes the received signal‐to‐noise ratio while keeping the interference levels below a certain threshold, and the third scheme (General Order Relay and User Selection) is based on iterative resource allocation algorithm. We derive exact closed‐form expressions of average bit error probability, outage probability, and average consumed power for the proposed schemes. Simulations are used to validate the analytical results. The results confirm the advantage of the proposed cooperation schemes in enhancing the system performance and improving the interference management. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In this paper, we introduce three cooperative communication schemes (BARS, GORUS, and BRS) with interference management for multi‐user cooperative wireless network. We derive exact closed‐form expression of average bit error probability, average outage probability, and average consumed power for the proposed schemes. The results confirm the analytical expressions and the advantage of the proposed schemes in enhancing the system performance and improving the interface management.